Gender Differences in Negative Experiences in Sport, Barriers to Participation in Sport, and Physical Activity in Junior High School Students In Bojonegoro - Ahmad Junaidi; Ahmad Lani; Rochsun Rochsun (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Although it has always been a factor influencing physical activity, it turns out that there have been no research reports on negative experiences in sport, Barriers to participation in sport, or physical activity of students in Indonesia. The purpose of this study was to generate knowledge about the negative experiences in sport, Barriers to participation in sport, and physical activity based on the gender of junior high school students in Bojonegoro Regency. The method used in this study is causal comparative correlation. The data used is taken from the Big Data Center for the study of physical literacy and sports education, Masters of Sports Education, IKIP Budi Utomo Malang. The population in this study was all junior high school students in Bojonegoro Regency, while the sample used was 846 respondents. To test the hypothesis, the researchers used the following techniques: descriptive analysis, a single mean test, two different means tests, and a correlation test. It was concluded that the negative experiences in sport did not exceed the tolerance limit, Barriers to participation in sport had met the tolerance limit, physical activity did not meet the eligibility criteria, there was no difference in negative experiences in sport, Barriers to participation in sport physical activity based on gender, and there was a relationship between negative experiences in sport and , Barriers to participation in sport. There is no relationship between negative experiences in sport and physical activity; there is a relationship between reasons for not exercising and physical activity.